The Role of Regional Owned Enterprises (BUMD) in Supporting the Financial Independence of a Region - Lisa Novita Hartanti; Rahmat Hidayat; Prilla Marsingga (Jurnal Ilmiah Wahana Pendidikan, 2022)
One of the important aspects in the implementation of regional autonomy is the issue of regional financial independence. BUMD becomes a business entity whose capital is wholly or most of the capital owned by the region as well as an increase in Regional Original Income (PAD). In the context of helping regional financial independence as well, the existence of BUMDs participates and participates in carrying out regional development in particular and national economic development in general in the context of a guided economy to meet the needs of the people by prioritizing industrialization and peace and pleasure in working within the company, towards a just, prosperous, fair society, and prosperous based on sound economic principles. Researchers used qualitative methods in the form of literature studies and reduced documentation, presented, then drawing conclusions. The performance of BUMD in regional financial independence is also considered to be very lacking. Many BUMDs in regions have a high dependence on central government assistance as well as on regional revenues and the basis for charging fees, which PAD provided is still not reliable for regions for regional autonomy, due to the relatively low level of taxes or levies in the regions.